Genetic diversity of Bacillus pumilus group causing trunk bulges on RRIM 3001 superclone rubber tree (Hevea brasiliensis Müll.Arg.) in Peninsular Malaysia - Azman Husni, Ainur Ainiah (2021)
Bacillus pumilus was identified as the pathogen in the initial outbreak of trunk bulges in RRIM 3001 superclone rubber plants in Serdang, Selangor. The occurrences of trunk bulges of RRIM 3001 superclone rubber trees eventually affect the quality and yield of natural rubber. Multilocus sequence analysis (MLSA) of five housekeeping genes (gyrB, pyrE, aroE, rpoB, and trpB) and repetitive elements-based polymerase chain reaction (rep-PCR) using REP, ERIC and BOX primers were conducted to analyze the diversity and systematic relationship of 20 isolates of B. pumilus group from four rubber tree plantations in Peninsular Malaysia (Serdang, Tanah Merah, Baling and Rawang). The analysis of all individual phylogenetic trees revealed the nearly congruent topology structure, with 75-100% bootstrap value across all 20 isolates of B. altitudinis and B. safensis. Both B. altitudinis and B. safensis are closely related to each other. Interestingly, none of the 20 bacterial isolates collected from the four collection areas were clustered together, indicating that variations between isolates from various geographical locations were significantly smaller than those between isolates from the same locations. Specifically, these 20 isolates were classified into two primary clusters: Cluster A, which contained 17 isolates of B. altitudinis, and Cluster B, which contained three isolates of B. safensis. The results were validated by a concatenated phylogenetic tree, which revealed that the isolates were divided into two clusters of B. altitudinis and B. safensis, with 98% and 100% bootstrap values, respectively. The dendrograms generated by REP-, ERIC-, and BOX-PCRs in rep-PCR analysis revealed that both species separated well. Compared to independent rep-PCR experiments, multi rep-PCR generates a high level of discrimination, while isolates of the two species remain separate in the corresponding dendrogram. The similarity coefficient observed among isolates in Cluster A (B. altitudinis isolates from Kedah, Kelantan and Rawang and five isolates from Serdang, ~35%) and Cluster B (three B. safensis isolates from Serdang, ~95%) from geographically separated states indicated that the isolates possibly were lineages of a single virulent isolate. The spread of these infections over Peninsular Malaysia was most likely due to transmission via planting stock. REP-PCR is the best approach for species grouping and separation since REP primers produced the most distinct fingerprinting pattern, followed by ERIC primer and BOX primer. The pathogens responsible for trunk bulges on RRIM 3001 superclone rubber trees in Peninsular Malaysia have been reclassified as B. altitudinis and B. safensis of the B. pumilus group. This finding would be a powerful platform for generating detailed documentation on the genetic diversity of B. pumilus group associated with RRIM 3001 trunk bulges in Peninsular Malaysia as well as developing disease control strategies to limit the spread of B. pumilus group species to new area.